Synovial Plica Syndrome of the Knee: A Commonly Overlooked Cause of Anterior Knee Pain - Lee, Paul Yuh Feng; Nixion, Amy; Chandratreya, Amit; Murray, Judith M. (The Surgery Journal, 2017)
Synovial plica syndrome (SPS) occurs in the knee, when an otherwise normal structure becomes a source of pain due to injury or overuse. Patients may present to general practitioners, physiotherapists, or surgeons with anterior knee pain with or without mechanical symptoms, and the diagnosis can sometimes be difficult. Several studies have examined the epidemiology, diagnosis, and treatment of SPS. We review these resources to provide an evidence-based guide to the diagnosis and treatment of SPS of the knee.
Keywords: plica; knee; synovial shelf syndrome; anterior knee pain